Chromosomal characterization of amazonian freshwater stingrays with evidence for new karyomorphs and xx/xy sex chromosomes - Valentim, Francisco Carlos Souza de; Porto, Jorge Ivan Rebelo; Feldberg, Eliana (Genetics and Molecular Biology, 2019)
Cytogenetic studies in the subfamily Potamotrygoninae have provided valuable insights into the understanding of the evolution and diversification of its species. In the present study, the chromosomal features of seven nominal potamotrygonin species are provided: Plesiotrygon iwamae (2n=74, FN=120), Potamotrygon amazona (2n=66, FN=107), P. constellata (2n=66, FN=110), P. leopoldi (2n=64, FN=102), P. motoro (2n=66, FN=106) from four different localities, and P. orbignyi (2n=66, FN=106), P. scobina (2n=66, FN=104), from Central Amazon. Additionally, we found a new karyomorph in P. wallacei. We considered the localization of Nucleolus Organizer Regions (NORs), as well as the pattern of constitutive heterochromatin, as species-specific characters. We found an XX/XY sex chromosome system in P. orbignyi, and we suggest that P. scobina and P. amazona also possess the same sex chromosome system. Overall, the chromosomal evolution in this group appears to have progressed towards a reduction in diploid number, with a concomitant increase in the number of bi-armed and nucleolar chromosomes. © 2019, Brazilian Journal of Genetics. All rights reserved.
Keywords: Chromosome Analysis; Chromosome Nor; Controlled Study; Female; Freshwater Species; Freshwater Stingray; Heterochromatin; Karyotype 46,xx; Karyotype 46,xy; Karyotype Evolution; Karyotyping; Male; Nonhuman; Plesiotrygon Iwamae; Potamotrygon Amazona; Potamotrygon Constellata; Potamotrygon Leopoldi; Potamotrygon Motoro; Potamotrygon Orbignyi; Potamotrygon Scobina; Potamotrygon Wallacei; Taxonomy